Development of an offshore response guidance tool for determining the impact of SSDI on released gas and benzene from artificial subsea oil well blowout simulations. (November 2022) - Socolofsky, Scott A.; Jun, Inok; Boufadel, Michel C.; Liu, Ruixue; Lu, Youyu; Arey, J. Samuel; McFarlin, Kelly M.
Abstract: We present an analysis of 2225 simulations of artificial oil well blowouts in nearshore and offshore waters of Newfoundland, Canada. In the simulations, we coupled the VDROP-J and TAMOC models to simulate the fate and transport of oil and gas from the release to the sea surface. Simulations were conducted with and without subsea dispersant injection. We analyzed the simulation database to quantify the mass fraction of oil and gas that surfaces, the mass fraction of released benzene that surfaces, and the horizontal offset to the surfacing zone. These data are also synthesized to yield empirical correlations to predict these output metrics from key input parameters. These correlations are summarized in an excel spreadsheet that allows rapid evaluation of spill dynamics with minimal initial knowledge of spill details. We call this tool an offshore response guidance table, which allows exploration of spill dynamics under diverse spill and response options. Highlights: Coupled a model for bubble and droplet size distributions with a nearfield integral plume model Analyzed database of 2225 simulated artificial well blowouts in nearshore and offshore Canadian waters Developed correlations between simulation output variables and model inputs Synthesized results into a spreadsheet-based offshore response guidance table